THE IMPACT OF COMMUNITY-BASED NUTRITIONAL SUPPORT ON QUALITY OF LIFE AND DIETARY BEHAVIOR AMONG OLDER ADULTS IN MALANG CITY: DUKUNGAN GIZI BERBASIS KOMUNITAS TERHADAP KUALITAS HIDUP DAN DIET LANSIA DI KOTA MALANG - Rani Rakhmawati; Ananda Sagita Maharani; Nadia Rahmi Amelia Pratiwi; Tama Mega Nawangwulan (Darmabakti Cendekia: Journal of Community Service and Engagements, 2026)
Background: Malnutrition, as well as suboptimal dietary patterns, are prevalent among community-dwelling older adults and strongly associated with lower functional capacity and quality of life. Community-based nutrition interventions are a strategic action to promote healthy ageing. Objective: To measure the impact of a community-based nutrition support program on quality of life and dietary patterns in older adults. Method: A pre–post intervention, conducted from June to December 2025 and involving 30 older adults, was guided by Yayasan Rumah Zakat Indonesia. The eight-week program involved nutritional screening using the MNA-SF, structured nutrition education, personalized dietary counseling, and assistance with healthy meals. All data were analyzed by a paired-T test or a Wilcoxon signed-rank test (α = 0.05). Results: There was a significant overall improvement in quality of life (p = 0.001). There were significant improvements also in dietary pattern scores (p < 0.001). Program evaluation showed high ratings for food quality, participant satisfaction, and perceived program impact. Conclusion: The intervention significantly enhanced multidimensional well-being and dietary behavior in community-dwelling older adults, underscoring the relevance of integrated nutrition support in promotive and preventive geriatric care; longer interventions and strengthened family involvement are recommended to sustain outcomes.